STUDI PENYELENGGARAAN PROGRAM PENDIDIKAN ANAK USIA DINI (PAUD) DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) KEDONDONG SAMARINDA - Sari, Adinda Novantri Pamungkas; Dwiyono, Yudo; Winarti, Hepy Tri (Universitas Negeri Jakarta, 2023)
This study aims to determine the management of the implementation of the Early Childhood Education program at PKBM Kedondong. This research is a type of qualitative research with a descriptive approach. The data and data sources in this study are managers, staff and educators, while the subjects of the study are places and events. Data collection techniques in this study were by observation, interviews and documentation. The results of the study found that the management of the implementation of the Early Childhood Education Program (PAUD) at PKBM Kedondong included the planning of early childhood education programs which were carried out through the process of identifying community needs for the importance of early childhood education programs so that PAUD was formed at PKBM Kedondong. From these needs, the formulation of the program was carried out so as to facilitate the formulation of the ECCE program, namely PAUD Kebun Kita at PKBM Kedondong. The implementation of the program is carried out through a learning process in early childhood and there is also a parenting activity. Furthermore, there is supervision and evaluation. Influencing factors include adequate facilities and infrastructure, the quality and adequacy of educators. There is educator coaching and also coaching for parents through parenting programs. In addition, the implementation process was hampered due to the Covid-19 pandemic which made changes in the learning system.